2020
DOI: 10.1111/nph.16973
|View full text |Cite
|
Sign up to set email alerts
|

CERBERUS is critical for stabilization of VAPYRIN during rhizobial infection in Lotus japonicus

Abstract: Summary CERBERUS (also known as LIN) and VAPYRIN (VPY) are essential for infection of legumes by rhizobia and arbuscular mycorrhizal fungi (AMF). Medicago truncatula LIN (MtLIN) was reported to interact with MtVPY, but the significance of this interaction is unclear and the function of VPY in Lotus japonicus has not been studied. We demonstrate that CERBERUS has auto‐ubiquitination activity in vitro and is localized within distinct motile puncta in L. japonicus root hairs and in Nicotiana benthamiana leaves.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…The punctate localization of RPG is similar to that reported for MtLIN and LjCERBERUS (Liu et al, 2019b; Liu et al, 2021). We hypothesized that RPG and CERBERUS may function together to promote IT formation.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The punctate localization of RPG is similar to that reported for MtLIN and LjCERBERUS (Liu et al, 2019b; Liu et al, 2021). We hypothesized that RPG and CERBERUS may function together to promote IT formation.…”
Section: Resultssupporting
confidence: 86%
“…CERBERUS contains a U-box domain and has auto-ubiquitination activity (Yano et al, 2009; Liu et al, 2021). CERBERUS interacts with LjVPY1/2, but promotes LjVPY1/2 accumulation in N. benthamiana and L. japonicus (Liu et al, 2021). Despite persistent efforts, we were unable to express and purify RPG from Escherichia coli , and RPG expression in N. benthamiana was too low to perform an in vitro ubiquitination assay for CERBERUS and RPG.…”
Section: Discussionmentioning
confidence: 99%
“…For M. truncatula , it has been shown that vapyrin (MtVPY), putative E3 ligase Lumpy infections (MtLIN), and cytoplasmic exocyst subunit EXO70H4 are part of a symbiosis-specific mechanism required for polar growth of infection threads [ 21 ]. Recently, it was shown that LjCerberus stabilizes LjVPY1 and LjVPY2 into trans-Golgi network/early endosome vesicles [ 174 ]. In addition, the Rhizobium-directed polar growth ( MtRPG ) gene is involved in the spatial subcellular reorganization in M. truncatula , encoding a protein belonging to the family of plant-specific proteins with a specific RPG-related proteins (RRP) domain and coiled-coil domain [ 175 ].…”
Section: Propagation Of the Infection Threadmentioning
confidence: 99%
“…Given the fact that VPY-recruitment into infectosome structures is abolished in an rpg mutant, it is tempting to speculate that RPG serves as a specificity determinant for infectosome- related endo- and exocytotic events during RNS, which is supported by the transcriptional dependency of RPG from NIN (Liu et al, 2019a; Soyano & Hayashi, 2014) and is in line with RPG being one of the few essential factors that have been lost in non-nodulating species of the FaFaCuRO clade (Griesmann et al, 2018; van Velzen et al, 2018). Upon recruitment of VPY into the infectosome complex it is further stabilized by LIN (Liu et al, 2019b) and this can also be assumed for CERBERUS, the ortholog of LIN in L. japonicus , which has been shown to stabilize VPY protein levels (Liu et al, 2021). Different to RPG , the genes encoding for VPY and LIN are retained in angiosperm species forming intracellular symbioses (Radhakrishnan et al, 2020) and at least VPY is additionally required for intracellular accommodation of the fungal partner during arbuscular mycorrhizal symbiosis (Feddermann et al, 2010; Pumplin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%